2017
DOI: 10.7466/jkhma.2017.35.2.77
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Family-Friendly Policies, Work-Life, Family-Life, and Intention of Childbirth

Abstract: This study is to examine the influence of family-friendly policies on married female workers'desire for an additional child and the mediating effects of family-friendly policies and birth intention on the relationship between work-and family-life.A questionnaire survey was conducted with married female women who were under the age of 40 years and with young children, using convenience sampling. Initially, a total of 400 survey questionnaires were distributed and 326 of them were gathered and analyzed as final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…First, items that belong to Quadrant I, have both high importance and satisfaction, and thus must maintain and manage the current level are 'healthy hobbies and productive leisure activities', 'exchange and harmony between neighbors and communities', 'learning effects of the plant cultivation process', 'mitigation of urban heat island and global warming', 'expansion of green area ratio', 'relieving stress by encountering nature', 'increasing self-esteem through plant cultivation', and 'health improvement effects through exercise and walking'. This result seems to reflect the awareness that urban agriculture may contribute to creating an urban environment and a community culture through leisure activities and green space (Cho and Kim, 2009) and can have a significant effect on improving physical and mental health (Hawkins et al, 2011;Harada et al, 2021). This indicates that, to promote urban agriculture, continuous management is necessary so that it is possible to maintain a positive perception and satisfaction toward socio-cultural functions, environmental-ecological functions, and health functions.…”
Section: Ipa For Values Of Urban Agriculturementioning
confidence: 61%
“…First, items that belong to Quadrant I, have both high importance and satisfaction, and thus must maintain and manage the current level are 'healthy hobbies and productive leisure activities', 'exchange and harmony between neighbors and communities', 'learning effects of the plant cultivation process', 'mitigation of urban heat island and global warming', 'expansion of green area ratio', 'relieving stress by encountering nature', 'increasing self-esteem through plant cultivation', and 'health improvement effects through exercise and walking'. This result seems to reflect the awareness that urban agriculture may contribute to creating an urban environment and a community culture through leisure activities and green space (Cho and Kim, 2009) and can have a significant effect on improving physical and mental health (Hawkins et al, 2011;Harada et al, 2021). This indicates that, to promote urban agriculture, continuous management is necessary so that it is possible to maintain a positive perception and satisfaction toward socio-cultural functions, environmental-ecological functions, and health functions.…”
Section: Ipa For Values Of Urban Agriculturementioning
confidence: 61%
“…In this case, all 60 participants lived with at least one parent-in-law in their family. Many previous studies [ 17 , 78 ] indicated that the conflicts caused by the relationship with in-laws always increased tension and the number of arguments in the family. In this study, based on the sharing from the participants, the researcher categorized three types of arguments, discrimination, and blaming from family members, which were conflicts with in-laws, blaming from husbands, and ignorance from children [ 39 , 40 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the high levels of stress and negative working conditions, less than 210,000 nursing practitioners are currently working in the health and welfare sectors and facilities [ 16 ]. In other words, more than 100,000 registered nurses are not working in the medical and nursing profession [ 16 ] due to various reasons, such as poor working environment, overload of responsibilities, and traditional family structure [ 17 ]. In order to encourage these registered nurses to return to the medical and nursing profession to tackle the ageing population, increasing demands of medical professional–patient ratio, the related Korean ministry established policies which attracted nearly 900 registered nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Environment, 2008;Kim et al, 2009). 정부가 가족 및 지역사 회와 연계하여 돌봄에 대한 지원을 강화하고, 지역사회에 대한 개 입을 통해 가족의 돌봄 부담을 해소시키겠다는 의지의 표명 이후 국내에서도 지역사회의 가족친화성에 초점을 맞춘 연구들이 진행 되었다 (Cha, 2010;Kim et al, 2009;Lee et al, 2012;Park, 2010). 이 연구들은 공통적으로 지역사회가 제공하는 돌봄 관련 시설과 서비스를 포함한 물리적 환경을 가족친화 지역사회의 구 성요소로 제안하였고 (Chin, 2018), 이후 실증연구들은 돌봄 관련 인프라를 잘 갖추고 있을 때 주민들은 그 지역사회를 가족친화적 으로 인식한다는 결과를 보고하였다 (Noh & Chin, 2012;Park, 2010;Yoo & Chin, 2013a).…”
Section: 김소영•유재언unclassified